Excitation of medium nuclei in the continuum region in inelastic scattering of deuterons - Grantsev, V.I.; Davydovskyy, V.V.; Kisurin, K.K.; Omelchuk, S.E.; Palkin, G.P.; Roznyuk, Y.S.; Rudenko, B.A.; Semenov, V.S.; Saltykov, L.S.; Slusarenko, L.I.; Struzhko, B.G.; Tartakovsky, V.K.; et al. (Вопросы атомной науки и техники, 2007)
Experiments on elastic and inelastic scattering of deuterons by ¹²C, ⁴⁸Ti, ⁵⁸;⁶⁴Ni nuclei at laboratory energy of 37 MeV for angles ranging from 16° to 61° were carried out on the U-240 isochronous cyclotron of the Institute for Nuclear Research, National Academy of Science of Ukraine. A broad maximum comprising the giant resonance in the spectrum of scattered deuterons for scattering angles less than 21° is observed at the nucleus excitation energies ranging from 12 to 30 MeV. The observed maximum was theoretically described in diffraction approximation after summing the cross-section over all final nucleus states. Виконано експерименти з пружного та непружного розсіяння дейтронів ядрами ¹²C, ⁴⁸Ti, ⁵⁸;⁶⁴Ni при енергії 37 МеВ на кути від 16° до 61° на ізохронному циклотроні У-240 Інституту ядерних досліджень НАН України. В енергетичному спектрі розсіяних дейтронів для кутів розсіяння менше 21° спостерігається широкий максимум при енергіях збудження ядер від 12 до 30 МеВ, який включає в себе максимум гігантського резонансу. Широкий максимум було описано теоретично в дифракційному наближенні після підсумовування перерізу за всіма кінцевими ядерними станами. Выполнены эксперименты по упругому и неупругому рассеянию дейтронов ядрами ¹²C, ⁴⁸Ti, ⁵⁸;⁶⁴Ni при энергии 37 МэВ на углы от 16° до 61° на изохронном циклотроне У-240 Института ядерных исследований НАН Украины. В энергетическом спектре рассеянных дейтронов для углов рассеяния меньше 21° наблюдается широкий максимум при энергиях возбуждения ядер от 12 до 30 МэВ, включающий в себя максимум гигантского резонанса. Широкий максимум был описан теоретически в дифракционном приближении после суммирования сечения по всем конечным ядерным состояниям.